2014
DOI: 10.1080/00221325.2014.917067
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers’ Motor and Verbal Self-Control Strategies During a Resistance-to-Temptation Task

Abstract: Although prior research has shown that young children exhibit enhanced self-control when they use verbal strategies provided through adult instructions, little work has examined the role of children's spontaneous verbalizations or motor behavior as strategies for enhancing self-control. The present study examined the usefulness of spontaneous verbal and motor strategies for 39 3- and 4-year-old children's ability to exercise self-control during a resistance-to-temptation task. After a 2-min play period, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…Gross (2015) describes situation selection as "taking actions that make it more or less likely that one will be in a situation that one expects will give rise to desirable or (undesirable) emotions" (p.7). In a study with three-and four-year-olds, children were sometimes observed to walk away to increase the distance between themselves and the reward (Manfra et al 2014). In fact, in this study, 61% of the children who succeeded in a 3-min delay task showed such 'moving away' behaviours, while this was only the case for 6% of the children who failed the task.…”
Section: Behaviours Subserving Effective Self-controlmentioning
confidence: 56%
See 4 more Smart Citations
“…Gross (2015) describes situation selection as "taking actions that make it more or less likely that one will be in a situation that one expects will give rise to desirable or (undesirable) emotions" (p.7). In a study with three-and four-year-olds, children were sometimes observed to walk away to increase the distance between themselves and the reward (Manfra et al 2014). In fact, in this study, 61% of the children who succeeded in a 3-min delay task showed such 'moving away' behaviours, while this was only the case for 6% of the children who failed the task.…”
Section: Behaviours Subserving Effective Self-controlmentioning
confidence: 56%
“…Consistent with previous findings from the early childhood literature and theoretical models which center on self-distractions and active avoidance of the reward as key to effective self-control (Duckworth et al 2016;Metcalfe and Mischel 1999), we coded whether children engaged in attention and verbal self-distractions, increased the distance between themselves and the reward, and/or made the action through which the reward could be reached more effortful. In keeping with the early childhood literature (e.g., Manfra et al 2014), we refer to these behaviours as attention, verbal, and motor behaviours from here on.…”
Section: Behaviours Subserving Effective Self-controlmentioning
confidence: 99%
See 3 more Smart Citations